Is It Understanding or Behaviour that Influence People to Use Cryptocurrency? - Ary Novianto, Robertus; Wijaya, Aida; Gandhi, Andrian (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to determine the influence of understanding of cryptocurrency and behavior toward risk on the intention to engage in cryptocurrency transactions. This study attempted to investigate the basic reason why people would use the cryptocurrency. This research used open-ended and closed-ended questionnaires to gather data and then regress the correlation between variables. The findings showed that both understanding of cryptocurrency and behaviour toward risk had significantly influenced the intention to use it. This could help the Indonesian government in considering whether it is necessary to regulate cryptocurrency in order to make people feel more secure in using cryptocurrency. Then probably cryptocurrency would sustain itself in the future and could support the nation in boosting the economy.